Calcium-Sensing Receptor Antagonist NPS-2143 Inhibits Breast Cancer cell Proliferation, Migration and Invasion via Downregulation of p-ERK1/2, Bcl-2 and Integrin β1 and Induces Caspase 3/7 Activation - Mohammad A.Y. Alqudah; Marwah Azaizeh; Aref Zayed; Leen Asaad (Tabriz University of Medical Sciences, 2022)
Purpose: Calcium-sensing receptor (CaSR) has been associated with breast cancer metastasis tothe bone. Targeting chemoattractant factors, such as calcium, that are released in response tobone resorption could prevent metastasis and induce apoptosis of cancer cells. In the presentstudy, we investigated the potential caspase 3/7 activation following treatment with a CaSRantagonist, NPS-2143, in breast cancer cells. In addition, the effects of NPS-2143 on breastcancer cell proliferation, migration and invasion were assessed.Methods: Colorimetric MTT assay was used to evaluate cell viability. Apo-one homogeneouscaspase-3/7 assay was used to measure caspase 3/7 activities in breast cancer cells. Cellmigration and invasion were assessed using scratch wound assay and matrigel invasionchambers, respectively. The protein expressions of p-ERK1/2, integrin β1 and Bcl-2 wereevaluated using western blotting.Results: Our study revealed that NPS-2143 significantly reduced cell proliferation with halfmaximal (50%) inhibitory concentration (IC50) values of 4.08 and 5.71 μM in MDA-MB-231and MCF-7 cells, respectively. NPS-2143 induced caspase 3/7 activation in MDA-MB-231 breastcancer cells which was accompanied with a remarkable reduction in the expression of Bcl-2antiapoptotic protein. NPS-2143 suppressed migratory and invasive abilities of MDA-MB-231cells with a significant reduction in the expression of p-ERK1/2 and integrin β1 proteins.Conclusion: Our study confirms the ability NPS-2143 to suppress proliferative, migratory andinvasive effects of breast cancer cells which was accompanied by caspase 3/7 activation andsuggests the potential of NPS-2143 as a promising anti-cancer molecule in breast cancer.